Buddhism and American thinkers - Inada, Kenneth K.; Jacobson, Nolan Pliny (State University of New York Press, 1984)
These essays by leading scholars explore Buddhist influences on the currents of American thought and show how Buddhism has made ever-deepening penetrations into the very substratum of American thinking. Each of the contributors relates Buddhism to a factor in American thinking, exploring the new ways in which Buddhist perspectives on personal identity, human suffering and alienation, the nature of compassionate love and social nature of ultimate reality amplify and clarify perspectives found in the golden age of American philosophy. The similarities are evident in the thoughts of William James, Josiah Royce, Alfred North Whitehead, John Dewey, Charles Sanders Peirce and Charles Hartshorne. ISBN 0-87395-754-7 (pbk.) : $9.95.